Penatalaksanaan Pasien Laki-Laki Usia 59 Tahun dengan Hipertensi Urgensi Melalui Pendekatan Kedokteran Keluarga - Zulia Yasminanindita Fahmi; Azelia Nusadewiarti (Medula, 2023)
Hypertension is one of the biggest causes of morbidity in the world, often referred to as the silent killer. The prevalence of hypertension in Indonesia in 2018 based on Basic Health Research (Riskesdas) with a population of approximately 260 million increased by 34.1% compared to 2013. According to data from the Lampung Provincial Health Office in 2021, the prevalence of hypertension in South Lampung is 24.8% of the total population aged ≥ 15 years is 762,894 people. The purpose of this case report is to implement holistic and comprehensive family doctor services by identifying risk factors, clinical problems, and patient management based on Evidence Based Medicine with a patient centered and family focused approach. This study is a case report. Primary data were obtained through autoanamnesis, physical examination, and home visits. Secondary data were obtained from the patient's medical record. Mr. M, 59 years old, had a chief complaint of difficulty sleeping since 1 day ago. Internal risk factors in the patient are male gender, 59 years old, a history of smoking since 39 years ago, a mother with a history of hypertension, a curative treatment pattern, and the patient's lack of knowledge about: hypertension classification where the patient does not know he is included in hypertension urgency; risk factors that cause the disease; complications that may occur; how to control the disease. External risk factors in the patient are: lack of family knowledge about the patient's disease, risk factors, complications, and prevention and control of the disease in the family and economic stress due to crop failure losses. Diagnosis and management of patients have been carried out holistically, patient centered, family focused, and community oriented. Changes in the clinical, knowledge, and behavior of patients and their families occurred after the intervention was given.